If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(x+1)+5=13-2(1-3x)
We move all terms to the left:
6(x+1)+5-(13-2(1-3x))=0
We add all the numbers together, and all the variables
6(x+1)-(13-2(-3x+1))+5=0
We multiply parentheses
6x-(13-2(-3x+1))+6+5=0
We calculate terms in parentheses: -(13-2(-3x+1)), so:We add all the numbers together, and all the variables
13-2(-3x+1)
determiningTheFunctionDomain -2(-3x+1)+13
We multiply parentheses
6x-2+13
We add all the numbers together, and all the variables
6x+11
Back to the equation:
-(6x+11)
6x-(6x+11)+11=0
We get rid of parentheses
6x-6x-11+11=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| 2(2b-1)=15 | | C(x)=0.85x+8 | | w=3/8=1/4 | | 4t+2+5t-8t=3+6 | | 18x+25=24x+13 | | 60+132d-36=-d+7 | | X=525-(63-5x) | | 4t+2+5t-8t=0 | | (5x+9)=(3x+5) | | 0=-16x^2+36x-20 | | 4x^2-16x^2+16=0 | | (5x+10)=(8x-14) | | 5(n+6)+20=20 | | 5y+7=4y+10 | | (5x+9)(3x+5)=0 | | x/8=0.3 | | 165=58-y | | 5x+65=95 | | 9x-13=4x-2 | | 23b^2+85b+26=-4-2b^2 | | 3.26c=8 | | 3g=6+4g | | 20+312n=30+234n | | 5(20=p)=2(30+p) | | 15x-21=3(5x-7) | | 3/7c+4=1/7c-6 | | x/8=4.5=12 | | 19c+31=26c-24 | | 12.3=4.41x | | 77x-49=7 | | 6x-(5×+8)=-3 | | 25+6n=18+7.50n |